Marketing of sweet jelly seeds of palmyra fruit: A study covering the tribal region of South Gujarat, India - Chaudhari, D. J.; Singh, Narendra (Journal of Plantation Crops, 2021)
Palmyra is a naturally occurring vegetation in Gujarat’s southern region, spread randomly overall soil and land types. The major produce utilized from palmyra palm for a livelihood by the tribal community, contributing considerably to their income, is through sales of the immature soft jelly seed nuts of the fruit called “galeli”. The present investigation was carried out to study the marketing cost, margin, and price spread in galeli marketing. Primary data for the period initiating from 2015-16 to 2017-18 were pooled from 50 palmyra palm growers selected randomly representing five tribal villages of Mahua taluka of Surat district in the South Gujarat region. Two marketing channels viz., Channel-I: producer-consumer and Channel-II: producer - retailer - consumer were observed, and the marketing cost incurred on galeli marketing in these channels was worked out, which was `51.64 and 33.94 per hundred galeli, respectively. The highest producer’s share in consumer’s rupee was worked out in channel-I. The study showed that the major constraint faced by 78 per cent of the palmyra palm growers in the marketing of galeli was the poor functioning of the climber equipment and non-remunerative prices for galeli in the local market.